2011
DOI: 10.1093/aobpla/plr029
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of the rare Pyreneo-Cantabrian endemic Aster pyrenaeus (Asteraceae)

Abstract: Background and aimsAster pyrenaeus (Asteraceae) is an endangered species, endemic to the Pyrenees and Cantabrian Mountain ranges (Spain). For its long-term persistence, this taxon needs an appropriate conservation strategy to be implemented. In this context, we studied the genetic structure over the entire geographical range of the species and then inferred the genetic relationships between populations.MethodologyMolecular diversity was analysed for 290 individuals from 12 populations in the Pyrenees and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…How do patterns of genetic diversity and the structure of natural populations relate to past geological and climate events? In order to answer these questions we employed intersimple sequence repeat (ISSR) markers, which have been widely used to detect genetic diversity in plants (Ge et al, 2005a;Sica et al, 2005;Meloni et al, 2006;Alam et al, 2009;Escaravage et al, 2011;Gürkök et al, 2013). The ISSR technique presents several advantages: high reproducibility due to long primers that permit the use of stringent annealing temperatures (45-60 °C) and high polymorphism, including within a species (Pradeep Reddy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…How do patterns of genetic diversity and the structure of natural populations relate to past geological and climate events? In order to answer these questions we employed intersimple sequence repeat (ISSR) markers, which have been widely used to detect genetic diversity in plants (Ge et al, 2005a;Sica et al, 2005;Meloni et al, 2006;Alam et al, 2009;Escaravage et al, 2011;Gürkök et al, 2013). The ISSR technique presents several advantages: high reproducibility due to long primers that permit the use of stringent annealing temperatures (45-60 °C) and high polymorphism, including within a species (Pradeep Reddy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Direct comparison of our results with other studies is problematic, since genetic diversity depends on numerous factors such as life-history traits, geographic range, and even the type of molecular method used (Nybom 2004). Nevertheless, in the group of endemic taxa of rocky/mountainous habitats we find several examples of species characterized by high genetic variability, for example Aster pyrenaeus (Escaravage et al 2011), Astragalus albens (Neel 2008), Campanula sabatia (Federica et al 2012) or representatives of the genus Opisthopappus (Guo et al 2013). Further examples of species with high levels of genetic variability in the population are found in more widespread alpine species having topographically isolated populations inhabiting a harsh environment, such as Table 1 Fig .…”
Section: Discussionmentioning
confidence: 72%
“…Ligularia sibirica, Šmídová et al 2011; Saxifraga paniculata, Reisch et al 2003). Studies of this group of species can help improve our understanding of the effects of random genetic processes on the genetic structure of populations and on the survival and evolutionary potential of small isolated populations in nature (Schmidt and Jensen 2000;Escaravage et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This problem is exacerbated by a lack of information about the ecology of most rare and endangered species under previous or current conditions. This issue is even more severe for plants than vertebrates as they receive less research attention and conservation money (Escaravage, et al 2011;Schemke, et al 1994;Shapcott et al 2009;Zhao et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have also used genetic tools to examine the current status of rare (Cozzolino, et al 2003;Escaravage et al 2011;Shepherd and Perrie 2011;Young et al 1996), endangered (Rosas et al 2011;Young et al 1999) and common (Jacquemyn et al 2007;Schmidt et al 2009) plant species around the world. Based on such studies, a range of management strategies have be suggested 3 with some stressing the importance of genetically unique smaller populations (Jacquemyn et al 2007), some highlighting the importance of the largest populations, (Cozzolino, et al 2003;Young et al 1999) and others disregarding population size in exchange for an increase in connectivity (Escaravage et al 2011;Rosas et al 2011; Shepard and Perrie 2011) depending on study findings.…”
mentioning
confidence: 99%